Near patient chlamydia and gonorrhoea screening and treatment in further education/technical colleges: a cost analysis of the ‘Test n Treat’ feasibility trial - Sarah Kerry-Barnard; Susie Huntington; Charlotte Fleming; Fiona Reid; S. Tariq Sadiq; Vari M. Drennan; Elisabeth Adams; Pippa Oakeshott (BMC Health Services Research, 2020)
Abstract Background Community-based screening may be one solution to increase testing and treatment of sexually transmitted infections in sexually active teenagers, but there are few data on the practicalities and cost of running such a service. We estimate the cost of running a ‘Test n Treat’ service providing rapid chlamydia (CT) and gonorrhoea (NG) testing and same day on-site CT treatment in technical colleges. Methods Process data from a 2016/17 cluster randomised feasibility trial were used to estimate total costs and service uptake. Pathway mapping was used to model different uptake scenarios. Participants, from six London colleges, provided self-taken genitourinary samples in the nearest toilet. Included in the study were 509 sexually active students (mean 85/college): median age 17.9 years, 49% male, 50% black ethnicity, with a baseline CT and NG prevalence of 6 and 0.5%, respectively. All participants received information about CT and NG infections at recruitment. When the Test n Treat team visited, participants were texted/emailed invitations to attend for confidential testing. Three colleges were randomly allocated the intervention, to host (non-incentivised) Test n Treat one and four months after baseline. All six colleges hosted follow-up Test n Treat seven months after baseline when students received a £10 incentive (to participate). Results The mean non-incentivised daily uptake per college was 5 students (range 1 to 17), which cost £237 (range £1082 to £88) per student screened, and £4657 (range £21,281 to £1723) per CT infection detected, or £13,970 (range £63,842 to £5169) per NG infection detected. The mean incentivised daily uptake was 19 students which cost £91 per student screened, and £1408/CT infection or £7042/NG infection detected. If daily capacity for screening were achieved (49 students/day), costs including incentives would be £47 per person screened and £925/CT infection or £2774/NG infection detected. Conclusions Delivering non-incentivised Test n Treat in technical colleges is more expensive per person screened than CT and NG screening in clinics. Targeting areas with high infection rates, combined with high, incentivised uptake could make costs comparable. Trial registration ISRCTN58038795 , Assigned August 2016, registered prospectively.